KEPENTINGAN INGGRIS MENJUAL SENJATA KE ARAB SAUDI - Harahap, M. Oghie Nugraha; ", Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
International arms trade is a very profitable business for weapons-making countries. Britain is one of the world's leading arms makers. Most artificial weapons are sold to the Middle East. The largest importer of UK arms in the Middle East is Saudi Arabia. Saudi Arabs rely heavily on UK to supply their weaponry needs. The Saudi Arabian government and its coalition have fought against the uprising by the Houthi. The revolt committed by the Houthis against the Yemeni government has been in place since 2015. In the fight against the uprising, Britain became a country that exports arms to Saudi Arabia. One of the weapons used by Saudi Arabia to counter the Yemeni insurgency is a UK-made cluster bomb that killed civilians. This is contrary to the content of the treaties that have been ratified by the UK in 2014 namely Arms Trade Treaty article 1. Ratified agreement does not make the UK stop or reduce the sale of weapons to Saudi Arabia. This research uses a neorealism perspective which is then supported by Stephen M. Walt's alliance theory with several concepts such as national interests, balance of power, and bandwagoning. Later this study also used the nation-state level of analysis with a research focus on the interest of United Kingdom on selling weapons to Saudi Arabia. This research then formulates answers to research questions related to UK interests violating the rules in ATT by selling weapons to saudi arabia. There are three important points that make the UK keep selling its weapons to Saudi Arabia, first, establishing the stability of relations with Saudi Arabia, secondly, strengthening Saudi Arabia's political position towards Iran, and the third to maintain a balance of power in the Middle East.Keywords: Balance of Power, Bandwagoning, Alliance, National Interest, ATT.